2012
DOI: 10.1136/archdischild-2012-301628
|View full text |Cite
|
Sign up to set email alerts
|

Predicting death or major neurodevelopmental disability in extremely preterm infants born in Australia

Abstract: The NICHD outcome estimator was helpful in predicting mortality for inborn infants, 22-25 weeks' gestation, but was less precise for outborn infants. It overestimated the combined outcome of death or major disability in infants born in Victoria, Australia, in 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
0
13
0
7
Order By: Relevance
“…Available studies of the outcomes of preterm infants have reported varying data on survival, especially regarding the extremely preterm group , ranging from 35% (18) to 70% (1), and from 59% (18) to 81% (1) for those at 25 weeks of gestation. Differences in care practices at the limit of viability , different study periods as well as different study cohorts (all births vs. all livebirths) may contribute to the variations in reported survival rates .…”
Section: Discussionmentioning
confidence: 99%
“…Available studies of the outcomes of preterm infants have reported varying data on survival, especially regarding the extremely preterm group , ranging from 35% (18) to 70% (1), and from 59% (18) to 81% (1) for those at 25 weeks of gestation. Differences in care practices at the limit of viability , different study periods as well as different study cohorts (all births vs. all livebirths) may contribute to the variations in reported survival rates .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have advanced beyond risk factor analyses to develop and validate risk prediction models for use in routine care and to assist with the planning and provision of health care. The only known prognostic models developed and validated are based on survival and a composite outcome of neurodevelopmental impairment at 18 to 22 months . While these are of great value, it is also important to untangle the factors that are prognostic in each developmental domain, which may be very different to those predictive of a composite outcome.…”
mentioning
confidence: 99%
“…The only known prognostic models developed and validated are based on survival and a composite outcome of neurodevelopmental impairment at 18 to 22 months. [5][6][7] While these are of great value, it is also important to untangle the factors that are prognostic in each developmental domain, which may be very different to those predictive of a composite outcome. This is the third paper from a systematic review of risk factor analyses for poor neurodevelopmental outcomes in the following domains: motor function, cognition, behaviour, hearing, and vision.…”
mentioning
confidence: 99%
“…2 %, wenn es sich um einen Mehrlingsjungen ohne fetale Lungenreifung und einem Geburtsgewicht von 420 g handelt, gegenüber knapp 80 % bzw. 50 % für ein Einlings-Mädchen nach abgeschlossener fetaler Lungenreife mit einem Geburtsgewicht von 850 g. Die Vorhersagekraft des Algorithmus wurde für andere Kohorten in Bezug auf die Überlebensraten mit geringen Abweichungen bestätigt [25,26]. In Deutschland lagen im Jahr 2012 die Überlebensraten (AQUA-Bundesauswertung) [29] für Frühgeborene < 26 Wochen Gestationsalter und < 1 000 g Geburtsgewicht knapp 6 % höher als in der amerikanischen NICHD-Kohorte von 1998-2003 (67,7 vs. 62,0 %), allerdings besteht in Bezug auf Frühgeborene mit einem Gestationsalter von 22 Wochen kein signifikanter Unterschied in den Überlebensraten von 2012 an das AQUA-Institut gemeldeten Frühgeborenen und den zwischen 1993 und 2009 in den genannten US-amerikanischen Zentren aktiv versorgten Frühgeborenen [30] (23,2 vs. 20,4 %, p > 0,1).…”
Section: Rechtlicher Rahmen ▼unclassified
“…Maximalversorgung mit hohen Fallzahlen[27] wirken sich positiv, eine floride Infektion und Geburt außerhalb eines Perinatalzentrums negativ aus[26]. Unter Einbeziehung eines Teils dieser Faktoren lässt sich die Prognose weitaus besser abschätzen, als wenn nur das Gestationsalter Berücksichtigung findet.…”
unclassified